2003
DOI: 10.1108/01443570310496599
|View full text |Cite
|
Sign up to set email alerts
|

The formalisation of manufacturing strategy and its influence on the relationship between competitive objectives, improvement goals, and action plans

Abstract: This paper intends to contribute to a better understanding of manufacturing strategy content by describing and analysing the content and formalisation of manufacturing strategies, and by exploring the relationships between the formalisation of manufacturing strategy, business/competitive objectives, improvement goals, and action plans. The study is based on the data from the third International Manufacturing Strategy Survey, which was conducted in more than 20 countries. The analysis shows that in companies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
5
49
0
Order By: Relevance
“…The current study differs in the high ranking of low price; which could be explained by increasing international competition, particularly from newly industrialising countries such as China, India and Eastern European countries. The emphasis on cost by Irish manufacturers supports the findings of Acur et al (2003) who found that improvements in cost reduction scored very highly as a corporate objective. Table X shows the mean values and ranking of Cluster 2 of the current study with the caretaker cluster.…”
Section: Taxonomy Of Manufacturing Strategiessupporting
confidence: 78%
“…The current study differs in the high ranking of low price; which could be explained by increasing international competition, particularly from newly industrialising countries such as China, India and Eastern European countries. The emphasis on cost by Irish manufacturers supports the findings of Acur et al (2003) who found that improvements in cost reduction scored very highly as a corporate objective. Table X shows the mean values and ranking of Cluster 2 of the current study with the caretaker cluster.…”
Section: Taxonomy Of Manufacturing Strategiessupporting
confidence: 78%
“…Although there is a suggested method of collecting data (including focusing on better companies; searching for companies by mail and/or phone; sending out the questionnaire to one contact person per company, usually a plant or manufacturing manager, in printed form; following up to help and inspire each contact person to fill out the questionnaire), it is up to the national research team to make decisions regarding this procedure. For further details regarding the survey, see the summary book on IMSS-I (Lindberg et al, 1998) or any of the articles that used data from previous rounds of the survey (e.g., Frohlich and Westbrook, 2001;Acur et al, 2003;Husseini and O'Brian, 2004;Laugen et al, 2005, Cagliano et al, 2006.…”
Section: The Surveymentioning
confidence: 99%
“…According to Acur (2003) and Kim, Lee and Yun (2004), organizations must have a broader platform that includes superior service to boost customer satisfaction. The latest addition to the competitive priorities is innovation denoting the ability to develop new products and implement new technologies and processes that create new markets (Brown, Squire, & Blackmon, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%